Temporal changes in serum creatine kinase concentration and degree of muscle rigidity in 24 patients with neuroleptic malignant syndrome - Nisijima K (Dove Medical Press, 2013)
Koichi Nisijima, Katutoshi ShiodaDepartment of Psychiatry, Jichi Medical University, Tochigi, JapanAbstract: Neuroleptic malignant syndrome (NMS) is a dangerous adverse response to antipsychotic drugs. It is characterized by the four major clinical symptoms of hyperthermia, severe muscle rigidity, autonomic dysfunction, and altered mental state. Serum creatine kinase (CK) elevation occurs in over 90% of NMS cases. In the present study, the detailed temporal changes in serum CK and degree of muscle rigidity, and the relationship between CK concentration and degree of muscle rigidity over the time course from fever onset, were evaluated in 24 affected patients. The results showed that serum CK peaked on day 2 after onset of fever and returned to within normal limits at day 12. Mild muscle rigidity was observed before the onset of fever in 17 of 24 cases (71%). Muscle rigidity was gradually exacerbated and worsened until day 4 after onset of fever. These findings confirm physicians' empirical understanding of serum CK concentrations and muscle rigidity in NMS based on data accumulated from numerous patients with the syndrome, and they indicate that serum CK may contribute to the early detection of NMS.Keywords: neuroleptic malignant syndrome, creatine kinase, muscle rigidity